2021
DOI: 10.3389/fimmu.2021.752042
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Function and T-Cell Receptor Repertoire Diversity: Implications for Patient Response to Checkpoint Blockade Immunotherapy

Abstract: The capacity of T cells to recognize and mount an immune response against tumor antigens depends on the large diversity of the T-cell receptor (TCR) repertoire generated in the thymus during the process of T-cell development. However, this process is dramatically impaired by immunological insults, such as that caused by cytoreductive cancer therapies and infections, and by the physiological decline of thymic function with age. Defective thymic function and a skewed TCR repertoire can have significant clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 132 publications
1
13
0
Order By: Relevance
“…Therefore, we conjectured that the predictive value of PTPRD/PTPRT differed between monotherapy and combination therapy, and further exploration is warranted. In this study, PTPRD/PTPRT mutant patients had higher TMB (6), MSI score (8), and TCR score (37), and were positively correlated with ICI treatment. DDR (38) and MMR gene mutations (39), which can increase tumor immunogenicity and promote anti-tumor immunity, were more frequent in the PTPRD/PTPRT mutant cancer patients than in the WT patients.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Therefore, we conjectured that the predictive value of PTPRD/PTPRT differed between monotherapy and combination therapy, and further exploration is warranted. In this study, PTPRD/PTPRT mutant patients had higher TMB (6), MSI score (8), and TCR score (37), and were positively correlated with ICI treatment. DDR (38) and MMR gene mutations (39), which can increase tumor immunogenicity and promote anti-tumor immunity, were more frequent in the PTPRD/PTPRT mutant cancer patients than in the WT patients.…”
Section: Discussionsupporting
confidence: 48%
“…In this study, PTPRD/PTPRT mutant patients had higher TMB ( 6 ), MSI score ( 8 ), and TCR score ( 37 ), and were positively correlated with ICI treatment. DDR ( 38 ) and MMR gene mutations ( 39 ), which can increase tumor immunogenicity and promote anti-tumor immunity, were more frequent in the PTPRD/PTPRT mutant cancer patients than in the WT patients.…”
Section: Discussionmentioning
confidence: 57%
“…Regarding anti-PD-(L)-1 therapies, some authors have also described an association of higher peripheral diversities at baseline with better outcomes, both using anti-PD-1 [ 117 , 128 , 129 ] and anti-PD-L1 [ 131 ], but the opposite associations have also been reported [ 119 ]. It has also been suggested that the efficacy of ICI therapies may be associated with age, as elderly people present a reduced thymic functionality and a lower peripheral TCR diversity [ 137 ]. This would be in concordance with the idea that more diversified TCR repertoires increase the likelihood of tumour antigens recognition.…”
Section: The Tcr Repertoire As a Predictive Biomarker Of Immune Check...mentioning
confidence: 99%
“…Clonal expansion of T cells measured by sequencing TCR beta chains also precedes Ipilimumab toxicity [ 153 ]. Drugs which enhance thymic function and TCR diversity may play a role in improving response rates to ICI [ 154 ].…”
Section: Novel Biomarkers Of Response Resistance and Toxicitymentioning
confidence: 99%